Intervening Role of Performance-Based Budgeting in the Relationship between Transformational Leadership, Organizational Commitment and University Performance - Suryo Pratolo; Arifin Hamsyah Mukti; Hafiez Sofyani (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2021)
This study aims to investigate the influence of transformational leadership and organizational commitment on performance-based budgeting systems of Indonesian universities. It also examines the impact of performance-based budgeting systems on universities' performance and the role of performance-based budgeting as an intervening variable. The population in this study was private universities registered in Indonesian Higher Education Service Institutions (or Lembaga Layanan Pendidikan Tinggi/ LLDikti) region XIII Aceh, Indonesia. The samples were selected using convenience sampling method. There were 130 completed questionnaires collected and analyzed using Partial Least Square. This study found that transformational leadership and organizational commitment have no direct effect on university performance, while the performance-based budgeting system has a significant positive effect on the performance of universities. This study also found that a performance-based budgeting system serves as an intervening variable in the relationship between transformational leadership and organizational commitment concerning higher education performance.